PERFORMANCE ASSESSMENT INSTRUMENT DEVELOPMENT IN BIOLOGY PRACTICUMS AT SENIOR HIGH SCHOOL - Al Muhajir, Muhammad (International Conference on Cultural Studies, 2019)
This study is research and development (R & D) which aims to develop an instrument used to assess student performance in practical activities. The development of performance assessment instruments refers to the 4-D development model developed by Thiagarajan which consists of four stages of development consisting of define, design, develop and disseminate. Based on the results of validation from experts and the results of input and responses from biology teachers, it shows the performance assessment instruments are classified as valid, practical and efficient and can be applied in assessing student performance in biology practicum activities.